KERR, Malcolm H., y YASSIN, El Sayed: Rich and Poor States in the Middle East: Egypt and the New Arab Order. - Cruz Questa, Carmen de la (Cuadernos de Historia Moderna y Contemporánea, 1986)
Sin resumen